Effect of reinforcement grade and concrete strength on seismic performance of reinforced concrete bridge piers. (1st November 2019) - Su, Junsheng; Wang, Junjie; Li, Zhongxian; Liang, Xiao
Highlights: Ten large-scale RC piers (circular and rectangular) were tested using quasi-static loading. Use of high-strength steel bars (HSSB) with equal volume enhance seismic behavior of RC piers. RC piers show comparable seismic behavior when using HSSB with equal strength replacement. Circular piers provide better restraint to bar buckling and thus show better seismic behavior. Rectangular piers are more sensitively than circular piers to concrete compressive strength. Abstract: This paper experimentally investigates the effect of the yield strength of longitudinal steel bars and concrete compressive strength on the seismic performance of reinforced concrete (RC) bridge piers. Cyclic loading tests of ten large scale RC bridge piers (including five circular section and five rectangular section) with different longitudinal steel bars grades (varying among HRB335, HRB500E and HRB600) and concrete compressive strengths (i.e., 32.6 MPa and 48.2 MPa) were conducted. Two different steel replacement methods, i.e. equivalent volume and equivalent strength replacements, were adopted for comparison. The seismic performance indexes lateral bearing capacity, deformation capacity, hysteretic energy dissipation and residual displacement were compared and analyzed. The test results indicate that all RC bridge piers show typical flexural failure mode while circular piers show better deformability and hysteretic energy dissipation than rectangular piers. Replacing conventional steel bars HRB335 with same amount of high-strength longitudinal steel bars (HRB500E and HRB600) (i.e. equivalent volume replacement) will increase the lateral bearing capacity (as expected), the yield displacement and the total deformation. Due to the increase in yield displacement, the displacement ductility, the viscous damping ratio and the residual displacement will reduce to some extent. Still, the RC piers reinforced with high-strength steel bars (HSSB) show larger plastic deformation and hysteretic energy dissipation because of greater total deformation and bearing capacity. The transverse reinforcement configurations of circular section provide better restraint to the buckling of longitudinal steel bars than rectangular section, thereby RC bridge piers with circular section show better deformability and hysteretic energy dissipation than rectangular section. The increase in concrete compressive strength reduces the yield displacement, thus enhances the hysteretic energy dissipation and viscous damping ratio at same total deformation. It is worth noting that the effect of concrete compressive strength on the seismic performance of rectangular section is more remarkable than circular section. Replacing conventional longitudinal steel bars with reduced amounts of high-strength steel bars (i.e. equivalent strength replacement) provided comparable flexural strength and deformation capacity, but reducing the residual displacement and hysteretic energy dissipation.